Relationship Pattern of S1 PGSD Students’ Learning Readiness and Academic Integration for Distance Education Management in Remote Islands - . Suhartono; . Suroyo (International Conference on Education and Language (ICEL), 2013)
This study was conducted to explore the pattern of S1 PGSD-UT students' learning readiness at two UT’s regional offices.  The results of the study were intended to develope  the guidelines of the Strata 1- basic education teacher Program at Universitas Terbuka (UT). The research was carried out in the islands of Kepulauan Seribu which managed by UT’s regional office in Jakarta  and the islands of Tidore which managed by UT’s regional office in Ternate. The data were collected using questionnaires to 200 basic education student-respondents and direct interviews to 27 student-respondents who registered in the first semester of 2010. The number of 174 questionnaires were analyzed. The results of the study showed that, first, about 92% of Strata 1-students of the basic education teacher program were elementary school teachers. Second, they lived in small islands and tended to face various obstacles to fully participate in learning activities which could influence on their success in their study completion. Third, about 48 % of the them dealed with infrastructure and facility limitations. Fourth, geographical, weather/natural,  economic, and  transportation conditions were possible  to  affect their learning readiness to fully involve in learning process. These conditons might increase student drop out and prohibit student completion in the proper time. Fifth, students’ confidence tended increase when they performed more self learning and had opportunity  to get more access to learning resource facilities. The student could be more success in learning by involving lecturers/tutors and facilitating communication media through an integrated mobile learning.